1992
DOI: 10.4269/ajtmh.1992.47.383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Deficiency on Granuloma Formation, Liver Fibrosis, and Antibody Responses in Experimental Schistosomiasis

Abstract: The influence of various dietary zinc levels on the fibrotic aspects of granuloma formation and on the humoral response to schistosome egg antigens was investigated in C57Bl/6 mice by feeding groups of animals zinc-deficient diets. At six weeks of age, control and zinc-deficient mice were exposed individually to 50-60 cercariae of the Brazilian LE strain of Schistosoma mansoni. The animals were maintained on their respective diets for eight weeks postinfection, then all animals were killed and analyzed for bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…Although there is no evidence to support this observation in the present investigation, the two studies are not directly comparable as mice were killed 8 weeks postinfection in one (Nawar et al, 1992) and 12 weeks post-infection in the other. Although the conventional, quantitative techniques are inherently biased, it is likely that the relatively small granulom as measured by Nawar et al (1992) reflect a true reduction in peak size of granulomas in zinc-deficient mice at 8 weeks post-infection, the result of impaired T-cell function. However, impaired T-cell function could also lead to impaired resolution of granulom as as well as impaired modulation of granulom atous hypersensitivity (Colley, 1975).…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Although there is no evidence to support this observation in the present investigation, the two studies are not directly comparable as mice were killed 8 weeks postinfection in one (Nawar et al, 1992) and 12 weeks post-infection in the other. Although the conventional, quantitative techniques are inherently biased, it is likely that the relatively small granulom as measured by Nawar et al (1992) reflect a true reduction in peak size of granulomas in zinc-deficient mice at 8 weeks post-infection, the result of impaired T-cell function. However, impaired T-cell function could also lead to impaired resolution of granulom as as well as impaired modulation of granulom atous hypersensitivity (Colley, 1975).…”
Section: Discussioncontrasting
confidence: 62%
“…The median granuloma volume per egg (about 8.6 nl for both groups) is therefore likely to be an overestim ate, although the value lies within the range (0.9± 28 nl) reported by Cheever (1965). Nawar et al (1992), using conventional methods to estim ate granulom a size, observed that zinc-deficient mice had relatively small granulomas. Although there is no evidence to support this observation in the present investigation, the two studies are not directly comparable as mice were killed 8 weeks postinfection in one (Nawar et al, 1992) and 12 weeks post-infection in the other.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Nonetheless, an increased stool volume is not a likely explanation of the difference in egg output since the weight gain was similar in the two groups over the 12 months study period (Friis et al, 1996). Effective formation of granulomata has been associated with facilitated excretion of the eggs (Doenhoff et al, 1986), and zinc deficiency has been shown to impair granuloma formation (Nawar et al, 1992). Hence, if this is the case in human infections, then it could have led to an underestimation of the true effect of zinc.…”
Section: Discussionmentioning
confidence: 95%